Prevalence of CT features of axial spondyloarthritis in patients with Crohn's disease. (May 2017) - De Kock, Isabelle; Hindryckx, Pieter; De Vos, Martine; Delrue, Louke; Verstraete, Koenraad; Jans, Lennart
Background: The sacroiliac joint and spine are seen on abdominal computed tomography (CT) and may show structural lesions as part of spondyloarthritis. Purpose: To determine the prevalence of CT features of spondyloarthritis in patients with Crohn's disease (CD). Material and Methods: A retrospective study of structural lesions of spondyloarthritis on abdominal CT was performed. The sacroiliac joints and spine of 120 patients were studied: study group I consisted of 40 patients with known CD and inflammatory back pain, group II involved 40 patients with CD without inflammatory back pain, and group III consisted of 40 patients without known joint or inflammatory bowel disease. Recorded CT features included sclerosis, erosions or ankylosis of the sacroiliac joint, enthesopathy, spinal syndesmophytes, and costovertebral joint lesions. Results: CT showed structural lesions of the sacroiliac joints in 19/40 (48%) patients with CD and inflammatory back pain (sclerosis [n = 14; 35%], erosions [n = 14; 35%], ankylosis [n = 3; 8%]), in 8/40 (8%) patients with CD without inflammatory back pain (sclerosis [n = 3; 8%], erosions [n = 4; 10%], ankylosis [n = 3; 8%]), and in 3/40 (8%) patients without known joint or bowel disease (sclerosis [n = 2; 5%], ankylosis [n = 1; 3%]). Syndesmophytes were exclusively seen in group I (n = 6; 15%). Conclusion: CT of the abdomen in patients with CD and inflammatory back pain shows structural lesions of the sacroiliac joint, entheses, or spine in almost half of the patients. Awareness and knowledge of these findings may guide the referring clinician to further clinical evaluation, imaging, and biomarker evaluation of the disease.